-6x-6(0)=36

Simple and best practice solution for -6x-6(0)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-6(0)=36 equation:


Simplifying
-6x + -6(0) = 36

Multiply -6 * 0
-6x + 0 = 36

Anything times zero is zero.
-6x + 0 = 36

Reorder the terms:
0 + -6x = 36
Remove the zero:
-6x = 36

Solving
-6x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-6'.
x = -6

Simplifying
x = -6

See similar equations:

| 10-(3z-5)=1-4z | | N+2(3-1)=8 | | w+w-w+4w+w=18 | | 15m-4m-2m-8m=17 | | 0.625=N+0.25 | | -5y=-15x-12 | | X=2[13+(8-5)] | | 8+0.2(x-300)=36.60 | | 2(4x-3)-6= | | w-w+2w+2w-3w-1=14 | | 2x+30=-3x | | ln(x)=.67 | | .5x+1=1.5x-8 | | 1500=x(1+.05)18 | | 8p-6p=20 | | 2n+1=2*1 | | -.5x-5=-11 | | 8(-48x-36)=-10(12-8x) | | 6j-4j=14 | | 5x+3=9x+15-x | | -7u-6u+-4u=17 | | 2014-5x=-41 | | 6x-8(0)=-48 | | 6x-13=-5x-2 | | 16w-3w-10w-3w+-4w=20 | | 16w-3w-10w-3w+-4w=10 | | 3N=123 | | 6v-3v+5v-7=9 | | 18y=6x-18 | | -2-6y=6 | | 8b-8b+2b=12 | | -3(5t-3)+5t=6t-4 |

Equations solver categories